Folklore and Mythological Symbolism of Lunar Images in the Poetry of Vasyl Holoborodko - Цепкало, Тетяна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article considers the interpretation of the lunar symbols of V. Goloborodko’s poetry in the folklore and mythological context. The poetry of this representative of the Kyiv School is analyzed in line with mythological representations of both world culture and ethno-national mental principles. The mythological thinking of the artist is represented through the verbal poetical system of images, axiology and ontology concepts, etc. The article establishes that, in the interpretation of the lunar mythology, V. Holoborodko refers to fairy tales, fantasy elements, folk symbols, magical and ritual actions, transfigurative metamorphoses, etc. The simile metaphors in the author’s artistic texts are decoded through explanations of the author’s individual cosmology. It is determined that the lunar symbols in the poetry of the "Kyiv man" are capable of transforming into objects, can float in water, magically affect nature and man, health and vigor, interact with spirits, dryads, mermaids, transform into a sensual image. In the poems by V. Golobolrodko, the symbol of the Moon is used in the texts that are stylized as folklore (fairy tales, legends, rituals, spells, etc.). Irrational perception of the image of the Night Orb becomes the basis for modeling the myth-poetic world picture of the representative of the Kiev School of Poetry. The paper proves that the myth-making of any writer is implemented through the ethno-mental foundations of the worldview, the archaic genomes of humanity, folk-poetic components, the collective subconscious and the empirical personal experience of the artist. Particular sensual images in poetic works operate in line with ancient ideas and beliefs, analytical and visual cogitative process, individual perception of concepts and the surrounding reality, specific emotional state. Lunar symbols in the poetry of V. Holoborodko are interpreted in conjunction with other verbal poetic images traditionally inherent in Ukrainian folklore.